PENGARUH KEWAJARAN HARGA DAN CITRA PERUSAHAAN TERHADAP KEPERCAYAAN DAN LOYALITAS KONSUMEN - MAHENDRA KUSUMA, AA. GEDE; Sukaatmadja, I Putu Gde (E-Jurnal Ekonomi dan Bisnis Universitas Udayana, 2018)
Based on data from the Association of Indonesian Motorcycle Industry (AISI) in 2016, Honda is a company that dominate the scooter market in Indonesia from year to year. This study aims to determine the role of reasonableness of price and corporate image to the trust and loyalty of consumers scooter Honda. Testing of research hypothesis using Structural Equation Modeling (SEM) analysis technique using AMOS 21 support, using IBM SPSS Statistics 22 for validity and reliability test. Samples of 100 respondents, taken using Purposive Sampling technique, with the criteria of respondents using Honda scooter continuously, at least for 1 last year, and live in Denpasar. The result shows that price fairness has positive significant effect to consumer trust. The image of the company has a significant positive effect on consumer's trust, price fairness has no significant effect on consumer loyalty, corporate image has a significant positive effect on consumer loyalty, and consumer trust has positive effect not significant to loyalty consumer.